Micromegas for beam loss monitoring. (April 2020) - Segui, L; Alves, H; Aune, S; Beltramelli, J; Bertrand, Q; Combet, M; Dano-Daguze, A.; Desforge, D; Dolenc-Kittelmann, I; Gougnaud, F; Joannem, T; Kebbiri, M; et al.
Abstract: The early detection of beam losses and the alarm to the machine protection system in accelerators are crucial for the safe operation of the machine. In the low energy region of the hadron accelerators, only neutrons and photons are produced in the case of a beam loss. However, photons are also emitted by electrons at the RF cavities, becoming a natural background for losses identification. A new kind of beam loss monitors have been conceived to extend the sensitivity to the low energy region of the high intensity hadron accelerators. They are based on Micromegas detectors sensitive to fast neutrons. The appropriate configuration of the Micromegas operating conditions will allow a fast response, a sensitivity to small beam losses and a suppressed sensitivity to photons. In this paper the operation principle and the system developed for the European Spallation Source will be presented, with focus on the results obtained at different irradiation facilities. First time proof of operation in real conditions, with the detection of beam losses, will be also shown with measurements performed at LINAC4 (CERN).